Impact of burning on soil organic carbon of maize-upland rice system in Mae Chaem Basin of Northern Thailand - Noppol Arunrat (2022)
Topsoil is the most sensitive to land management practices, and the application of fire has been used for clearing the land and burning crop residues in highlands. Thus, investigating the topsoil organic carbon density (SOCD) is crucial to improve the understanding of its impact. Four sites of highland maize-upland rice systems in the Mae Chaem Basin, Chiang Mai Province, Thailand were selected as study areas and investigated for two years. At each site, burnt and unburnt soil samples were collected separately from depths of 0–10, 10–20, and 20–30 cm. Results showed that burnt soil contained higher SOCD than unburnt soil, with average values of 75.0 and 71.4 Mg C ha−1, respectively; however, a significant difference was not detected. The SOCD of burnt soils increased in the first growing season after the burning 5 months due to the large amounts of ashes and black carbon left after the fire and decreased in the second growing season after the burning 10 months. Burning caused the fluctuation of SOCD, resulting in a slight increase of SOCD in burnt soils by 0.19 Mg C ha−1 year−1, whereas it steadily increased by 2.04 Mg C ha−1 year−1 in unburnt soils across the maize-upland rice system. This study pointed out that burning may not sustain the SOCD in the long term, especially in the highlands.